Contested Spaces: Intimate Segregation and Environmental Gentrification on Chicago's 606 Trail. (December 2020) - Harris, Brandon; Schmalz, Dorothy; Larson, Lincoln; Fernandez, Mariela; Griffin, Sarah
Abstract: The 606, a greenway in Chicago, has been lauded as a transformative revitalization project that provides diverse benefits and connects communities. However, the greenway has become a source of conflict among Latinx residents who question the trail's value and influence on their communities. Using observations and interviews with users and residents, this study examined potential consequences of The 606, including intimate segregation, which occurs when individuals use social and physical barriers to stratify themselves in a shared environment, and impacts of environmental gentrification. Results revealed division along The 606 with Latinx users isolating themselves in western trail segments, citing feelings of exclusion, discrimination, and resistance to gentrification. Conversely, white users were found to avoid western trail segments due to fear and pervasive stereotypes. The study highlights the urban park paradox, where green space provides benefits to communities while simultaneously generating unintentional consequences that potentially reinforce segregation and social inequities.